Severe aortic stenosis and familial hypercholesterolemia - Mallma Gómez, Milagros (2021)
Homozygous familial hypercholesterolemia (HFH) is a rare and life-threatening disease that can manifest as coronary artery disease or severe aortic stenosis before twenties. We present the case of a male adolescent who was hospitalized with a clinical diagnosis of HFH and severe aortic stenosis. He underwent aortic valve replacement with mechanical prosthesis and aortic annulus enlargement, and two aortocoronary bypasses were implanted due to an intraoperative complication. The patient evolved favourably and was discharged with combination therapy with high-intensity statins and ezetimibe.